2020
DOI: 10.1177/1077801219897846
|View full text |Cite
|
Sign up to set email alerts
|

Strengthening the Circle: An International Review of Government Domestic Violence Prevention Plans and Inclusion of Indigenous Peoples

Abstract: This study describes the level of government commitment in preventing domestic violence (DV) toward Indigenous women in countries of the Global North. Seventy-two government-endorsed DV prevention plans across 11 countries were analyzed. While more than half of the plans acknowledged Indigenous peoples, the main discourse reinforced a Western DV paradigm, reproduced negative stereotypes, and ignored systemic factors. Little consideration for intersectionality, the impact of colonization, or Indigenous worldvie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…While there is not a “one-size fits-all” solution, a handful of universities have been increasingly successful in creating institutional shifts within their unique university settings, including Georgia State University’s “Real Consent” program and Columbia University’s SHIFT study (Student Health Promotion, 2020 ; The Sexual Health Initiative to Foster Transformation, 2019 ). A component of building institutional trust includes hiring and retaining truly representative and diverse groups of faculty, staff and students (including male faculty) who are actively engaged in SVSH research and advocacy (Orenstein, 2020 ), comprehensive and exhaustive training of university staff and those responsible for SVSH prevention, mitigation (e.g., service providers, campus security), and thinking about diversity and inclusion as inseparable from violence prevention (Fotheringham et al, 2020 ; Marine & Nicolazzo, 2017 ; Terrazas-Carillo et al, 2019 ). Institutional culture change is rooted in shared accountability.…”
Section: Discussionmentioning
confidence: 99%
“…While there is not a “one-size fits-all” solution, a handful of universities have been increasingly successful in creating institutional shifts within their unique university settings, including Georgia State University’s “Real Consent” program and Columbia University’s SHIFT study (Student Health Promotion, 2020 ; The Sexual Health Initiative to Foster Transformation, 2019 ). A component of building institutional trust includes hiring and retaining truly representative and diverse groups of faculty, staff and students (including male faculty) who are actively engaged in SVSH research and advocacy (Orenstein, 2020 ), comprehensive and exhaustive training of university staff and those responsible for SVSH prevention, mitigation (e.g., service providers, campus security), and thinking about diversity and inclusion as inseparable from violence prevention (Fotheringham et al, 2020 ; Marine & Nicolazzo, 2017 ; Terrazas-Carillo et al, 2019 ). Institutional culture change is rooted in shared accountability.…”
Section: Discussionmentioning
confidence: 99%
“…Victims are also not protected by the state. A study that reviewed government plans in 11 countries found that they ignore, minimize or misrepresent IPV in indigenous communities (Fotheringham et al, 2020). The authors concluded that with the absence of preventive strategies and specific actions and few changes, community problems are resolved or not in the community itself (Fotheringham et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Empowerment and advocacy work is inherently political, as it must address system‐level policies that have continuously and programmatically denied BIWoC rights to have power and agency over their bodies and lives (Knitzer, 1976). Unfortunately, much work remains, as BIWoC women's movement efforts have less influence over government policies compared to White women (Fotheringham et al, 2021).…”
Section: Promoting Reproductive Justice Through Advocacy and Empowermentmentioning
confidence: 99%